Spectral Performance and Calibration of the Suomi NPP OMPS Nadir Profiler Sensor. Issue 12 (26th December 2017) - Pan, C.; Weng, F.; Flynn, L.
Abstract: The Ozone Mapping and Profiler Suite (OMPS) is one of five instruments on board the Suomi National Polar‐orbiting Partnership (Suomi NPP) satellite. As part of OMPS, the Nadir Profiler (NP) spectrometer measures Earth's albedo in ultraviolet wavelengths from 250 to 310 nm to profile Earth atmospheric ozone concentration. Since launch in 2011, many changes in the NP radiometric and spectrometric calibration have been made to improve sensor data quality. The most challenging issue is to characterize instrument on‐orbit spectral calibration and to maintain a stable spectral performance to meet sensor design criteria. Validation of the NP sensor data found an average of 3–5% error in the sensor albedo measurements that exceeded 2% requirement, creating 1–2% uncertainty in ozone profile. Data analysis attributes the error to prelaunch calibration uncertainty, ground‐to‐orbit dichroic changes, and on‐orbit detector wavelength registration drifts. A recent update of calibration significantly improved spectral wavelength knowledge as well as the accuracy of the measured solar spectra. As a result, the wavelength‐dependent albedo error is significantly reduced and generally meets the radiometric uncertainty requirement of 2%. Key Points: S‐NPP OMPS is the first of a series of flight units flying on the S‐NPP satellite to provide continuity with global ozone data for operational remote sensing of weather and other environmental applications The NOAA Calibration Team presents the most recent improvements to the sensor on‐orbit calibration; the wavelength‐dependent albedo error is significantly reduced and meets the radiometric uncertainty requirement of 2% in general Experience from this study presents reasonable and feasible opportunities for improving the backscattered ultraviolet (BUV) sensor products for the coming series of OMPS sensors in the next 20 years